Recipročni model izgorelosti (RMI) - Kukovec-Pšeničny, Andreja (Psihološka obzorja (Ljubljana), 2006)
Burnout can be described as chronic state of extreme psychophysical and emotional exhaustion. Burning out is a stage process consisting of: the stage of exhaustion, the stage of captivity and the final stage - adrenal burnout. Adrenal burnout syndrome (ABS) is the final stage of burning out process, resulting in a functional blocade of hypothalamic-pituitary-adrenal axis whichcauses secondary cortisol insufficiency. Even though they share similar symptoms, burnout and depression are two different types of disorder. They differ mainly in basic cortisol levels and self-esteem. Researchers tend to link the burnout syndrome and environmental stress (interpersonal causes). Recently, some of them found connection between burnout syndrome and personality traits (intrapersonal causes). Reciprocal burnout model links both causes. It shows that in the same circumstances only a few people suffer from adrenal burnout syndrome. It states that personal characteristics are oneof the main causes why people suffering from burnout syndrome enroll in nonreciprocal personal and professional relations. Socialization process playsan important role in development of personality traits. The core of the reciprocal burnout model consists of one's attitude towards his or her basic needs' fulfillment, personal system of values, and correlation between fulfillment of basic needs (energy accumulation) and burning out process (energy consumption). Reciprocal burnout model is opening a series of questions, concerning the connection between personality traits, life satisfaction and personal values, and burnout syndrome risk behavior, as well as the influence of whole life circumstances on burning out process.
Keywords: izgorelost; psihologija; psychology; potrebe; samopodoba; osebnostne lastnosti; vrednote